The role of the family doctor in endothelial dysfunction and metabolic syndrome comorbidities - Adriana TICĂRĂU (Romanian Journal of Medical Practice, 2016)
The prevalence of metabolic syndrome in the population register percent growth, which is why the role of the family doctor in preventive medicine becomes essential, one of its main objectives being the early detection of patients exposed to risk factors in order to prevent cardiovascular diseases. Closely linked to metabolic syndrome is endothelial dysfunction, as a result of its evaluation, it can be selected patients with metabolic syndrome, and patients who associated comorbidities: non-alcoholic fatty liver, hyperuricemia, polycystic ovary syndrome, sleep apnea.